Guramata āratī prabodha - Ditta Siṅgha, 1852-1901 (SAMP early 20th-century Indian books project, 1900)
Critique against popular mode of saying morning and evening prayers among Hindus, with a call for Sikhs to remain true to the concepts of prayer preached by the gurus.